Anti-cancer targeting telomerase inhibitors: β-rubromycin and oleic acid - Mizushina, Yoshiyuki; Takeuchi, Toshifumi; Sugawara, Fumio; Yoshida, Hiromi (Mini reviews in medicinal chemistry, 2012)
Telomerase is a ribonucleoprotein complex that elongates telomeric DNA and appears to play an important part in the cellular immortalization of cancers. In the screening of potent inhibitors of human telomerase, several inhibitors have been discovered from natural and chemical sources. Some compounds potently inhibit the activity of human telomerase. Rubromycins and fatty acids such as β-rubromycin and oleic acid, respectively, were found to be inhibitors of human telomerase. The IC(50) values of β-rubromycin and oleic acid were 8.60 and 8.78 μM, respectively. A kinetic study revealed that these compounds competitively inhibited the activity of telomerase with respect to the substrate of the primer and dNTP. The energy-minimized three-dimensional structure of β-rubromycin and oleic acid was calculated and designed. The V-shaped curve and molecule length of 18.7-20.3 Å in these compound structures were suggested to be important for telomerase inhibition. The three-dimensional structure of the active site of telomerase (i.e., the binding site of the primer and dNTP substrate) might have a "pocket" that could "join" these compounds. These results appear to suggest a potential structure for the development of more potent inhibitors of human telomerase.